2020
DOI: 10.1186/s12905-020-01101-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between factors related to the pregnancy, neonatal period, and later complications (especially asthma) and menarcheal age in a sample of Lebanese girls

Abstract: Background Studies about the majority of the factors that may potentially influence the pubertal timing and menarche were controversial. The objective was to evaluate the association between factors related to the pregnancy, neonatal period, and the complications that may happen later in life and the menarcheal age in a sample of Lebanese girls admitted or not to the NICU at birth. Our secondary objective was to try to find, for the first time in literature, a correlation between respiratory di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 63 publications
(97 reference statements)
1
3
0
Order By: Relevance
“…T A B L E 2 Estimated crude and adjusted odds ratios for the anthropometric measures overweight/obesity, tall stature and abdominal obesity in youth offspring, as predicted by maternal age at menarche (MAM) | 299 demonstrating a transgenerational effect of maternal early onset of puberty with offspring height and in contrast to a study in China which did not find a significant association. 26 Our sensitivity analysis by sex showed significant association only for boys which is consistent with a study in China 27 performed on adolescents (11)(12)(13)(14)(15)(16) years old) and in contrast to other previous studies who did not find a sex-specific association between MAM and offspring height. 15,19,26 This difference may be attributed to the smaller sample size in our study providing lower statistical power.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…T A B L E 2 Estimated crude and adjusted odds ratios for the anthropometric measures overweight/obesity, tall stature and abdominal obesity in youth offspring, as predicted by maternal age at menarche (MAM) | 299 demonstrating a transgenerational effect of maternal early onset of puberty with offspring height and in contrast to a study in China which did not find a significant association. 26 Our sensitivity analysis by sex showed significant association only for boys which is consistent with a study in China 27 performed on adolescents (11)(12)(13)(14)(15)(16) years old) and in contrast to other previous studies who did not find a sex-specific association between MAM and offspring height. 15,19,26 This difference may be attributed to the smaller sample size in our study providing lower statistical power.…”
Section: Discussionsupporting
confidence: 88%
“…It has been demonstrated that early MAM is associated with earlier puberty timing in offspring. 28 Early age of menarche in girls is associated with short stature 16,[29][30][31] and it is possible that it may attenuate the intergenerational impact of early MAM in postpuberty girls regarding growth to a tall stature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations